2014
DOI: 10.1039/c3cc48481e
|View full text |Cite
|
Sign up to set email alerts
|

A mild and selective Pd-mediated methodology for the synthesis of highly fluorescent 2-arylated tryptophans and tryptophan-containing peptides: a catalytic role for Pd0 nanoparticles?

Abstract: A Pd-mediated direct C-H bond functionalisation of tryptophan has been developed, both as a single amino acid residue and within peptides. Important mechanistic insight into this process has been gained by characterising a Pd catalytically competent nanoparticle phase which evolves during the early stages of reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 31 publications
0
88
0
6
Order By: Relevance
“…TEM analysis of this reaction mixture demonstrated PdNPs that were uniformly o5 nm in size, which suggested that Pd 0 species were catalytically relevant under these conditions (Fig. This methodology was subsequently applied to the direct C2-arylation of a protected tryptophan derivative, 76,77 whereupon the rapid propagation of PdNPs was observed within minutes. Subsequently, it was found that PhI(OAc) 2 rapidly degrades to PhI within 10 min at 150 1C in DMSO; correspondingly, use of PhI as the aryl coupling partner in place of the oxidising PhI(OAc) 2 had no effect on the yield of the reaction.…”
Section: Propagation Of Pdnps In C-h Bond Functionalisationsmentioning
confidence: 94%
“…TEM analysis of this reaction mixture demonstrated PdNPs that were uniformly o5 nm in size, which suggested that Pd 0 species were catalytically relevant under these conditions (Fig. This methodology was subsequently applied to the direct C2-arylation of a protected tryptophan derivative, 76,77 whereupon the rapid propagation of PdNPs was observed within minutes. Subsequently, it was found that PhI(OAc) 2 rapidly degrades to PhI within 10 min at 150 1C in DMSO; correspondingly, use of PhI as the aryl coupling partner in place of the oxidising PhI(OAc) 2 had no effect on the yield of the reaction.…”
Section: Propagation Of Pdnps In C-h Bond Functionalisationsmentioning
confidence: 94%
“…[208,209] Die Autoren verwendeten unsymmetrische Diaryliodoniumsalze als Arylierungsreagentien sowie Pd-(OAc) 2 als Katalysator und erreichten eine effiziente und selektive C-2-Arylierung von Tr yptophan bei 25 8 8C. [208,209] Die Autoren verwendeten unsymmetrische Diaryliodoniumsalze als Arylierungsreagentien sowie Pd-(OAc) 2 als Katalysator und erreichten eine effiziente und selektive C-2-Arylierung von Tr yptophan bei 25 8 8C.…”
Section: Angewandte Chemieunclassified
“…Anspruchsvollere Modifikationen natürlicher Proteine bedürfen üblicherweise eines elektrophilen Reagenzes,w elches selektiv mit einem natürlichen Pränukleophil, wie beispielsweise Tyrosin, Lysin oder Cystein, kuppelt. [73,74] Tryptophan-Arylierungen verlaufen in der Regel recht träge und erfordern unter Umständen harsche Reaktionsbedingungen (z. [53,64,65] Eine der ersten allgemeiner nutzbaren Anwendungen einer Kreuzkupplung auf natürliche Proteine war die tyrosinselektive Tsuji-Trost-Allylierung,w elche erstmals in Berichten von Francis und Mitarbeitern Erwähnung fand (Abbildung 10).…”
Section: Reduktive Aminalkylierung:n-terminus Lysunclassified